Dendritic phytic acid as a proton-conducting crosslinker for improved thermal stability and proton conductivity - Keiichiro Maegawa; Vellaichamy Joseph; Arthisree Devendran; Hassan Alipour; Krzysztof Łyczko; Yaroslav Korol; Hanna Lewandowska-Siwkiewicz; Atsushi Nagai (Communications Materials)
Abstract There is growing interest in materials that exhibit enhanced proton conductivity at elevated temperatures without the need for humidification. Here, we develop a dendritic proton-conducting dopant for proton exchange membranes based on phytic acid (PhA) salts. PhA, which contains six phosphate groups capable of facilitating proton exchange, interacts with 4-dimethylaminopyridine (DMAP). DMAP serves as a strong electron donor, making it highly reactive with PhA. In this endeavor, cellulose sulfonic acid was selected as the base proton exchange membrane. Notably, the dimethylamino group of DMAP on the surface of DMAP-PhA acts as a basic site, enabling acid-base interactions with the sulfonic acid groups of cellulose sulfonic acid. As a result, DMAP-PhA functions as a proton-conducting crosslinker, significantly improving the thermal stability of the composites and increasing proton conductivity by enhancing the degree of proton dissociation at each interaction site.